The Effect of Digital Interventions on Public Adherence to Vaccination Programmes - Trees; Sri Wahyuni; Sariestya Rismawati (Miracle Journal Get Press, 2025)
Digital interventions are increasingly emerging as innovative strategies to improve vaccination coverage. Purpose: study aims to further explore the influence of digital interventions on public compliance in vaccination programmes. Methods: The present study employed a quasi-experimental design to ascertain the impact of a digital intervention on vaccination compliance. Based on calculations using the Slovin formula with an error tolerance level of 5%, the required sample size was determined to be 400 respondents. Data were collected through an online survey before and after the intervention to assess changes in vaccination adherence. Data were analysed using inferential statistical methods, employing a logistic regression test to evaluate the relationship between the digital intervention and vaccination adequacy. Result: results showed that digital interventions had a significant effect on improving vaccination compliance from 55% to 78% (+23%, p  0.001) after the digital intervention. In addition, the level of public knowledge about vaccines increased by 25%, Conclusion: that technology-based strategies can be an effective tool in disseminating accurate health Implication: These findings provide important implications for policymakers and health workers in developing more structured digital-based vaccination programmes, as well as provide strategic recommendations for stakeholders in improving the effectiveness of these strategies.